Chemisorption of hydrogen sulfide over copper-based metal–organic frameworks: methanol and UV-assisted regeneration. Issue 9 (27th January 2021) - Gupta, Nishesh Kumar; Kim, Suho; Bae, Jiyeol; Kim, Kwang Soo
Abstract : H2 S adsorption and regeneration of Cu-based MOFs. Abstract : Three copper-based metal–organic frameworks (MOFs) with different organic linkers were synthesized for the removal of H2 S gas at room temperature. The synthesized MOFs were characterized by microscopic and spectroscopic techniques to understand their structural, functional, and optical properties. The H2 S adsorption capacity of MOFs calculated by column studies followed the trend: 105.6 mg g −1 (CuBDC) > 27.1 mg g −1 (CuBTC) > 1.3 mg g −1 (CuBDC-N) in dry conditions. The adsorption capacity increased in moist conditions due to an easy dissolution and dissociation of H2 S in a film of water. X-ray photoelectron spectroscopy confirmed the presence of sulfur bound to Cu-sites and sulfate ions. The spent MOFs were regenerated by the successive effect of methanol and low power UV-C radiation. The regenerated CuBTC showed an exceptionally high adsorption capacity of 95.6 mg g −1 in the second cycle, which was linked to the reactivation of Cu-sites and improved surface area and porosity. The regeneration process developed in this study is a cost-effective method to recycle chemisorbed MOFs without compromising with their structural and functional integrity.